Influence of a ground‐based VLF radio transmitter on the inner electron radiation belt. Issue 2 (28th February 2013) - Selesnick, R. S.; Albert, J. M.; Starks, M. J.
Abstract: [1] Observed signatures of electron precipitation from the inner radiation belt are shown to be consistent with the theory of resonant scattering by whistler‐mode plasma waves, assuming the waves originate in VLF radio transmissions from the ground station NWC. The conclusion is based on a stochastic model of electron transport that includes pitch angle diffusion, radial diffusion, energy loss, and azimuthal drift. The wave scattering causes an increase in quasi‐trapped electron intensity, forming the "wisp" signature, and a corresponding decrease in stably trapped intensity at low altitude. A smaller decrease at high altitude is expected to be obscured by inward radial diffusion. If NWC were shut down, the resulting increase in stably trapped electron intensity would be minimal. Key Points: VLF transmissions from the ground cause radiation belt electron precipitation Data are consistent with the theory of resonant scattering by whistler‐mode waves Influence of NWC ground station on stably trapped electron intensity is minimal